Structural and functional changes in erythrocytes associated with the development of thrombosis and disorders of hemostasis - M. V. Kruchinina; A. A. Gromov; E. V. Kruchinina (Атеросклероз, 2022)
The data of clinical and experimental studies of the last decade force us to reconsider the role of red blood cells in the development of thrombosis and disorders of the hemostasis system. This area is of particular relevance during the COVID-19 pandemic. The purpose of the review is to present data on the structural and functional changes in erythrocytes, on changes in their number associated with the development of thrombosis and hemostasis disorders, including in patients with coronavirus infection. The article presents the results of scientific research devoted to the study of morphological and functional changes in red blood cells that affect hemostasis and thrombosis. These changes include erythrocyte number or hematocrit (which modulates blood rheology through blood viscosity) and qualitative changes such as deformability, erythrocyte aggregation, expression of adhesive proteins and phosphatidylserine, release of extracellular microvesicles, hemolysis, piezo receptor status, modulation of nitric oxide bioavailability. Changes in the parameters of erythrocytes that occur during blood storage are shown, with possible thrombotic consequences during blood transfusion. The most recent research concerns changes in red blood parameters during SARS-CoV-2 infection that are associated with the development of thrombosis: virus attachment and amplification of viral proteins in erythropoiesis progenitor cells; activation of stress erythropoiesis with an increase in nuclear erythrocyte cell percentage up to 42 %; activation of the processes of oxidation of the protein band 3 with its excessive cleavage, oxidation and cleavage of the alpha-chain of spectrin, ankyrin; changes in the lipid architecture of the membrane and a decrease in the activity of erythrocyte antioxidants, which mediate disturbances in cell deformability and impaired ATP release; reducing the ability of red blood cells to secrete nitric oxide; decrease in the level of sphingolipids of the erythrocyte membrane; excessive production of microvesicles with tissue factor; an increase in erythrocyte rigidity with impaired release of intraerythrocyte nitric oxide due to SARS-CoV-2 virus attacking the hemoglobin 1-beta chain and porphyrin capture with potential heme inhibition; an increase on the surface of erythrocytes expression of activated complement components C3b and C4d, immunoglobulin IgG, which worsens cell deformability; attachment of erythrocytes through the Toll-like receptor 9 to neutrophil extracellular traps, which contributes to thrombosis; increased presentation of phosphatidylcholine on erythrocyte membranes, which facilitates the assembly of the tenase and prothrombinase complexes, contributing to the production of thrombin, an increase in intracellular calcium levels with stimulation of the formation of microvesicles with prothrombotic potential. The presented data indicate a significant role of changes in erythrocyte parameters in the development of hemostasis disorders, especially during the COVID-19 pandemic, which makes red blood cells a target for therapy and suggests a change in the emphasis of management tactics for patients with thrombosis.